Non alcoholic fatty liver disease. The new millennium pandemia (2010)
Non-alcoholic liver disease (NAFLD) is the most common liver disease in affluent societies, affecting 2-8% of the general population, and it will be soon in our societies. It is generally asymptomatic or with a no specific picture of fatigue, hepatic pain or discomfort and hepatomegaly. It is suspected in cases with aminotransferase or imaging abnormalities. Liver biopsy is considered the gold standard for diagnosis. There is a close pathogenic relationship with obesity, type 2 diabetes, hyperlipidemia, metabolic syndrome and insulin resistance. Approximately 20-25% of the cases progress into cirrhosis with all its complications including hepatocellular carcinoma and the need for liver transplantation. Correction of insulin resistance with dietary measures and physical activity is generally beneficial. The efficacy of the multiple medications available remains to be demonstrated. © 2010 Asociaciones Colombianas de Gastroenterologia, Endoscopia digestiva, Coloproctologia y Hepatologia.